CCAFS Regional Agriculture Forecasting Toolkit - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Reliable and timely crop yield forecasts is critical for informed planning and policy decisions on food production, marketing, export/import, distribution and the overall food security in the country. The conventional approach of crop yield forecasting is a time consuming, costly exercise and suffers from delays in processing the results.